2006
DOI: 10.1108/02686900610653008
|View full text |Cite
|
Sign up to set email alerts
|

Changing pattern of competitive disadvantage from disclosing financial information

Abstract: Purpose -To empirically examine the changing pattern of competitive disadvantage experienced by the reporting companies in disclosing segmental information in the Malaysian environment. Design/methodology/approach -The study consists of a final sample of 116 Malaysian companies listed on the Malaysian Bourse for the years 2000-2002. Four hypotheses were developed to investigate the relationship between segmental information disclosure and competitive disadvantage. Adopting weighted average correlation (WAC) te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 7 publications
(5 reference statements)
0
14
0
1
Order By: Relevance
“…Due to that they might discourage the higher disclosure. Finally, Santema et al (2005), Talha, Sallehhuddin and Mohammad (2006) and Lu et al (2007) mention the disadvantage of information disclosure. According to Santema et al (2005), general disclosure costs consist of the cost of gathering, processing and auditing and disseminating the information, as well as possible litigation costs and cost that might create competitive disadvantage.…”
Section: Asian Journal Of Finance and Accountingmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to that they might discourage the higher disclosure. Finally, Santema et al (2005), Talha, Sallehhuddin and Mohammad (2006) and Lu et al (2007) mention the disadvantage of information disclosure. According to Santema et al (2005), general disclosure costs consist of the cost of gathering, processing and auditing and disseminating the information, as well as possible litigation costs and cost that might create competitive disadvantage.…”
Section: Asian Journal Of Finance and Accountingmentioning
confidence: 99%
“…According to Santema et al (2005), general disclosure costs consist of the cost of gathering, processing and auditing and disseminating the information, as well as possible litigation costs and cost that might create competitive disadvantage. Talha et al (2006) who study the segmental reporting practice in Malaysia mention that the cost of disclosure includes competitor pressure, political pressure and customer pressure. Lu et al (2007) highlight that information disclosure may reduce shareholder value by revealing valuable information to competitors or by increasing legal costs for the firm even though they recognize the advantages of disclosure such as increase in institutional interest and liquidity of the firms and consequently there will be lower cost of capital and public relation benefits (Santema et al, 2005).…”
Section: Asian Journal Of Finance and Accountingmentioning
confidence: 99%
“…The relationship between disclosing financial information including segmental data and competitive disadvantage will be affected by the proprietary cost, where companies have an incentive to disclose more financial information to the market in order to reduce information asymmetry in the absence of proprietary costs (Talha et al, 2006).…”
Section: Competition Intensitymentioning
confidence: 99%
“…Reference [17] finds a significant positive relationship between voluntary disclosure and firm size, measured as the natural logarithm of total asset. References [18], [19] asserted that company size might have a substantial effect on the level of disclosure. Specifically, these aforementioned researches have reported that huge corporations have incentives of disclosing more segmental information.…”
Section: H3: There Is Association Between Diffusion Of Ownership and mentioning
confidence: 99%